Computational hemodynamic analysis of stenosed coronary artery / Sarfaraz Kamangar - Sarfaraz , Kamangar (2016)
The coronary artery disease is a leading cause of death all over the world. The primary cause of coronary artery disease is the arthrosclerosis. There are various causes of stenosis formation primarily linked to food habits. There has been continuously growing interest to understand the blood flow behaviour in Atherosclerosis condition due to its serious impact on human life. It is believed that hemodynamic plays an important role in further progression of these coronary artery diseases. In this study, an investigation of variation in hemodynamic and diagnostic parameters in the left coronary artery was carried out based on idealistic and realistic patient specific models of left coronary arteries in diseased and normal condition during hyperthermia. The CT scan images of suspected patients of coronary artery disease were acquired to reconstruct the 3D models of realistic left coronary models. Computational fluid dynamics is used to reflect the in vivo cardiac hemodynamic. The wall pressure, velocity flow pattern, and wall shear stress were calculated during the cardiac cycle. To investigate the effect of shapes of stenosis on hemodynamic and diagnostic parameters, three different shapes of stenosis models (elliptical, trapezoidal and triangular) are studied. The highest level of pressure drop was observed for trapezoidal shape of stenosis followed by elliptical and then by triangular shaped stenosis. The increase in percentage area stenosis, increases the velocity profile inside the blockage region. The variation in FFR in the region of 76.5-82.7% AS could lead to the misdiagnosis of intermediate stenosis to decide upon coronary intervention around the clinically used cut-off value of 0.75. The influence of angle of curvature of artery i.e. 300, 600, 900 and 1200 on hemodynamic parameters was investigated. It is found that the blood flow behaviour is substantially affected by the combined effect of stenosis and the curvature of artery. The presence of curvature provides low blood flow region at the lower wall of artery creating a potential stenotic region. The effect of different degree of stenosis on various locations in patient’s specific left coronary artery on hemodynamic parameters have been studied by using CT scan images during hyperemic conditions. The decrease in pressure was found downstream to the stenosis as compared to the coronary artery without stenosis. The velocity increases with the increase in the percentage area stenosis. The result also shows that the re-circulation zone was observed immediate to the stenosis and highest wall shear stress was observed across the stenosis. The maximum pressure drop was found for the models having stenosis of 70% and 90% at the left main stem and left circumflex branch respectively. Thus it can be conveniently said that the case of 70% AS located at left main stem and 90% AS at left circumflex is the most severe condition among 10 models being investigated.